PENGKLASIFIKASIAN DEBITUR DENGAN MENGGUNAKAN ALGORITMA GRAHAM SCAN DALAM PENGAPLIKASIAN CONVEX HULL - ARIESTA, AGUS EKA; GANDHIADI, G.K.; TASTRAWATI, NI KETUT TARI; KENCANA, I PUTU EKA NILA (E-Jurnal Matematika, 2013)
Computational geometry is the mathematical science of computation by using the algorithm analysis to solve the problems of geometry. The problems of computational include polygon triangulations, convex hulls, Voronoi diagrams, and motion planning. Convex hull is the set of points that form a convex polygon that covers the entire set of points. The algorithms for determining the convex hull, among others, Graham Scan, Jarvis March, and Divide and Conquer. In the two-dimensional case, Graham Scan algorithm is highly efficient in the use of time complexity. This article discusses the quest convex hull of the data bank debtors, some of the data used to look at the classification accuracy of the convex hull formed. The coordinates of all the data found by using principal component analysis.After the data are analyzed, we get the accuracy of classification by 74%.
Keywords: Computational geometry; convex hull; graham scan; principal component analysis